INSTRUMEN EVALUASI AFEKTIF SPIRITUAL - Amrina Anas; Julhadi Julhadi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
This article discusses affective spiritual evaluation instruments which include three main subtopics, namely observation, attitude scales, and self-assessment. The purpose of this study is to understand the concept and application of these instruments in early childhood Islamic education. The method used is literature review from various educational psychology and Islamic education sources. The results indicate that observation is useful for identifying behavioral changes, attitude scales help quantify students’ affective responses, and self-assessment supports students’ awareness and reflection of their own spiritual development. These three instruments complement each other in providing comprehensive affective-spiritual evaluations.Keywords: affective evaluation, spiritual, observation, attitude scale, self-assessment